2012
DOI: 10.1038/nm.2961
|View full text |Cite
|
Sign up to set email alerts
|

The sirtuin SIRT6 blocks IGF-Akt signaling and development of cardiac hypertrophy by targeting c-Jun

Abstract: Abnormal activation of insulin-like growth factor (IGF)-Akt signaling is implicated in the development of various diseases, including heart failure. However, the molecular mechanisms that regulate activation of this signaling pathway are not completely understood. Here we show that sirtuin 6 (SIRT6), a nuclear histone deacetylase, functions at the level of chromatin to directly attenuate IGF-Akt signaling. SIRT6-deficient mice developed cardiac hypertrophy and heart failure, whereas SIRT6 transgenic mice were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
424
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 415 publications
(446 citation statements)
references
References 46 publications
19
424
3
Order By: Relevance
“…Furthermore, the inhibition of IGF-Akt signaling by SIRT6 has also been implicated in protection from cardiac hypertrophy, whereas deacetylation of H3K9 mediated by SIRT6 is crucial for transcriptional suppression of IGF signaling-related genes (17). In concordance with these reports, our experiments using mutant SIRT6 H133Y demonstrated that deacetylation of H3K9 by SIRT6 was necessary for attenuation of IGF-Akt-mTOR signaling, and that wild type SIRT6 tended to suppress IGF-1R expression levels in HBECs (Fig.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Furthermore, the inhibition of IGF-Akt signaling by SIRT6 has also been implicated in protection from cardiac hypertrophy, whereas deacetylation of H3K9 mediated by SIRT6 is crucial for transcriptional suppression of IGF signaling-related genes (17). In concordance with these reports, our experiments using mutant SIRT6 H133Y demonstrated that deacetylation of H3K9 by SIRT6 was necessary for attenuation of IGF-Akt-mTOR signaling, and that wild type SIRT6 tended to suppress IGF-1R expression levels in HBECs (Fig.…”
Section: Discussionsupporting
confidence: 87%
“…A recent study demonstrated that SIRT6 regulates IGF-Akt-mTOR signaling through the suppression of IGF signaling-related genes (17). We therefore investigated the involvement of SIRT6 in regulation of the IGF-Akt-mTOR signaling pathway by detecting phosphorylated forms of IGF-1R, Akt, and p70 S6Kinase (S6K, a downstream signaling molecule of mTOR).…”
Section: Sirt6 Attenuates the Igf-akt-mammalian Target Of Rapamycin Smentioning
confidence: 99%
See 1 more Smart Citation
“…26 High levels of IGF-1 have been associated with heart failure and increased cardiac mortality. 64,65 Thus, it is postulated that downregulation of Gab1 is a result of increased IGF-1. Alternatively, the loss of Gab1 may be due to increased degradation through the ubiquitin-proteasome system.…”
Section: Resultsmentioning
confidence: 99%
“…Intriguingly, PTEN33 and CTMP exert the same effect in pathological cardiac hypertrophy induced by AngII. Except for CTMP, many molecules have been demonstrated to play crucial roles on cardiac remodeling induced by pressure overload by regulating AKT signaling 4, 35, 36, 37, 38, 39…”
Section: Discussionmentioning
confidence: 99%